Self-reported outcomes of patients undergoing total hip replacement surgery assessed by the WOMAC questionnaire - Di Nubila,Michele Ferreira de Souza (2011)
ABSTRACT Objective: To assess pain, stiffness and physical function outcomes among patients undergoing total hip replacement using the Western Ontario and McMaster Universities Osteoarthritis Index. Methods: From January 2009 to July 2010, 64 male and female patients were assessed using the WOMAC questionnaire at baseline, hospital discharge, 3-month follow-up, and 6-month follow-up; one group of patients with primary hip osteoarthritis (n = 42) and another group with hip fracture (n = 22). Results: Changes in the total scores of the osteoarthritis group were statistically significant comparing baseline, hospital discharge, 3-month and 6-month assessments, demonstrating continued improvement over time up to 6-month follow-up. The total scores of the hip fracture group demonstrated a worsening from baseline to discharge, followed by improvement. The differences were statistically significant between baseline and discharge, as well as between discharge and the 6-month assessment. No statistically significant differences were found between baseline values and the 3-month assessment or baseline values and the 6-month assessment, demonstrating that the patients returned to their baseline health status after 3 months and maintained this status up to 6-month follow-up. Conclusion: The Western Ontario and McMaster Universities Osteoarthritis Index questionnaire detected changes in outcome following hip replacement surgery among patients with primary diagnoses of hip osteoarthritis and hip fracture, with differences in the pattern of changes between the two groups.